Hubungan Pemberian Insentif Terhadap Peak Performance Pada Pemain Bola Basket Di Sma N 2 Padang - Hilmy Hardoni, Harits; Aulia, Prima (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
The purpose of this study is to determine the correlation of incentives provision towards peak performance in basketball players in SMA N 2 Padang. The method that used in this study is quantitative correlation. The technique that used in this study is saturated sample.The population in this study is basketball players in SMA N 2 Padang.There are 40samples in this study.The measuring instrument that used in this study is peak performance scale from the Fakhrurri scale based on Garfied and Bannett's theory and the scale of incentives provision is based on Nawawi's theory.The results showed a correlation coefficient of r = 0.599, p = 0,000 (p <0.05), showing that there is a very significant positive correlation between incentives provision and peak performance for basketball players in SMA N 2 Padang